The concept of Archipelago Islam: A Critical Historical Study - Hayani, Aida; Ari Dwi Rahmawati; Ika Tri Susilowati; Akhmad Zulfikar Kabibulloh; Mohd. Farhan (STAI Terpadu Yogyakarta, 2024)
Congress Nahdatul Ulama (NU) in Jombang, East Java which took place on August 1-5 2015. Since NU coined the term in 2015, the term “Islam Nusantara” has been widely misunderstood by several communities.